2010
DOI: 10.1002/ijc.25373
|View full text |Cite
|
Sign up to set email alerts
|

Alpha‐fetoprotein: A new member of intracellular signal molecules in regulation of the PI3K/AKT signaling in human hepatoma cell lines

Abstract: Despite its well-defined role as a serum growth factor during fetal liver development and hepatic oncogenesis, the biological significance of cytoplasmic alpha-fetoprotein (AFP) remains incompletely understood. Here, we provide evidence to illustrate that cytoplasmic AFP may function as a regulator in the phosphatidylinositol 3-kinase (PI3K)/AKT pathway in human hepatocellular carcinoma cells. The results demonstrated colocalization and interaction of AFP and phosphatase and tensin homolog deleted on chromosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
113
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 111 publications
(121 citation statements)
references
References 29 publications
8
113
0
Order By: Relevance
“…AFP has served as a useful biomarker for diagnosis of HCC since the 1970s, and currently is widely used in the clinical diagnosis of liver cancer. However, recent findings on the signal molecule-like roles of AFP have led to a re-evaluation of this protein [4][5][6][7]. AFP therefore can no longer be regarded merely as a diagnostic marker for HCC, but may now be understood as an intracellular factor which is involved both in ontogenetic and oncogenic growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AFP has served as a useful biomarker for diagnosis of HCC since the 1970s, and currently is widely used in the clinical diagnosis of liver cancer. However, recent findings on the signal molecule-like roles of AFP have led to a re-evaluation of this protein [4][5][6][7]. AFP therefore can no longer be regarded merely as a diagnostic marker for HCC, but may now be understood as an intracellular factor which is involved both in ontogenetic and oncogenic growth.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies showed that cytoplasmic AFP also blocks RA-RAR mediated expression of the growth arrest and DNA damage-inducible 153 gene (GADD153) and is responsible for the extent of cell survival [6]. In addition, cytoplasmic AFP was found to promote the PI3K/AKT pathway through interacting and interfering with PTEN protein which leads to aberrant growth of hepatocellular carcinoma cells [7]. These effects of cytoplasmic AFP were verified by knockdown of AFP mRNA with siRNA or overexpression of AFP by transfection of the afp gene in non-AFP producing cells.…”
Section: Introductionmentioning
confidence: 99%
“…The AKT/mTOR pathway is an intracellular signaling pathway important in regulating cell cycle, growth, and apoptosis. It had been previously shown that CyAFP initiated a signaling cascade that stimulated CXCR4 expression by activating the PI3K/AKT signaling pathway [48]. Zhu et al found that CyAFP colocalized and interacted with PTEN, thus inducing CXCR4 expression by activating AKT (Ser 473) phosphorylation.…”
Section: Cyafp Involvement In Intracellular Signaling and Regulationmentioning
confidence: 96%
“…In a second study, Li et al provided direct evidence that CyAFP functions as a regulator in the phosphatidylinositol-3-kinase (PI3K)/AKT pathway of Bel 7402 hepatoma cells [48,49]. PI3Ks are signal transducing enzymes capable of phosphorylating inositol involved in cell growth, proliferation, and cellular trafficking.…”
Section: Cyafp Involvement In Intracellular Signaling and Regulationmentioning
confidence: 99%
“…With its structural similarity to albumin, it has been hypothesized to play a role in the transport of serum components, including fatty acids, steroids, and heavy metals, and may serve as an embryonic analogue of albumin (2). There have also been reports of AFP interfering with intracellular signaling, including both caspase 3 and PI3K/AKT pathways (5, 6). An immunoregulatory role for AFP has also been proposed.…”
Section: Introductionmentioning
confidence: 99%